The new psychology of language from body to mental model and back - Dijkstra, Ton; Peeters, David (Routledge, an imprint of the Taylor & Francis Group, 2023)
"This illuminating book offers an up-to-date introduction to the psychology of language, exploring aspects of language processing that have previously not been given centre stage such as the role of body and brain, social aspects of language use, and mental models. This accessible book is essential reading for students in disciplines such as psychology, cognitive science and neuroscience, artificial intelligence, biology, the language and communication sciences, and media studies. It is also a useful resource for a lay audience with an interest in language and communication"--Provided by publisher.